Investigating Students’ Need Analysis on English Learning Materials for International Class Program (ICP) of Geography at Universitas Negeri Makassar - Nur Syamsi; Abdullah Abdullah; Muhammad Hasbi (Hasanuddin University, 2025)
This research is aimed to identify students' needs for English language learning in International Class Program (ICP) of Geography at Makassar State University. The main focus of this study is to investigate students’ learning needs and students’ target needs related to English learning materials. This research used a mixed-method approach by combining quantitative and qualitative data analysis. The number of participants in this study was 30 people, consisting of 28 second year ICP Geography students and 2 lecturers. Data collection instruments were questionnaires and interviews. The findings showed that the students need English learning materials that were relevant to their fields of study. Appropriate materials were considered to play an important role in improving students' English skills. Based on the learning need analysis, it was found that there are differences in English proficiency levels among students. Speaking and listening skills were considered the main skills that needed to be mastered because they were believed to support the English learning process more effectively. The most common problem faced by students was pronunciation errors. Analysis of target needs showed that students' learning styles are diverse, such as learning through reading, learning through videos or films, and learning in small groups. The main goals of students in learning English are related to future career aspirations and self-development. Efforts made by students to improve their English skills include memorizing English vocabulary, reading English texts, watching films, and listening to English music.